PENGARUH PERLAKUAN PEMATAHAN DORMANSI TERHADAP VIABILITAS BENIH AREN (Arenga pinnata Merr.) - Desy Manurung; Lollie Agustina P.Putri; Mbue Kata Bangun (Universitas Sumatera Utara, 2013)
The objective of this research were to study the influence of dormancy breaking methods on sugarpalm seed viability. This research was conducted at screenhouse in Agriculture Faculty, Universityof North Sumatera, Medan (± 25 m asl) from June-September 2012, using completely randomizeddesign with 8 treatments (control, water soaking 50ºC, 0.1%KNO3, 0.3%KNO3 , 0.5%KNO3 and0.1%HCl, 0.2%HCl, 0.3%HCl) with 4 replications. The results showed that dormancy breakingmethods were significantly effect to axis embryo length (5 week after planted), germinating time,viability, plant height, diameter bar, numbers root, root length, fresh weight, dry weight and werenot significantly to axis embryo length 4 WAP, normal sprout, abnormal sprout and the numberleaf extent.Keywords : dormancy, sugar palm,viability